Self-Assembly of Fibrinogen in Aqueous, Thrombin-Free Solutions of Variable Ionic Strengths - Hämisch, Benjamin (Langmuir : the ACS journal of surfaces and colloids, 2019)
Fibrinogen not only forms fibrin networks if assisted by thrombin but also exhibits self-assembly in dilute aqueous solutions in the absence of thrombin. It could be shown that self-assembly can be triggered in a controlled way by diluting the ionic strength set to a value of 0.14 M NaCl in the starting solutions. The present work unravels the mechanism of this self-assembly process by means of a combination of time-resolved multiangle static and dynamic light scattering and atomic force microscopy. Analysis was carried out as a function of the ionic strength adjusted by the drop in ionic strength and at variable salt compositions at a given final ionic strength. Composition was varied by changing the ratio of NaCl and phosphate buffer. The self-assembly induced by the drop of the ionic strength depends on the final value. The lower the final ionic strength gets, the faster is the self-assembly process. The variation of the salt composition at a given ionic strength has only a marginal effect, which depends on the ionic strength. The self-assembly obeys a step-growth process, where any intermediate cluster can coalesce with any other cluster. Interpretation of the data with a kinetic model based on the approach of von Smoluchowski follows a diffusion-limited cluster aggregation at ionic strength values lower than 30 mM. At an ionic strength of 30 mM, the model has to take into account a size dependence of the rate constant, and at 60 mM a transition is observed to a reaction-limited cluster aggregation